Immersion Into Noise - Nechvatal, Joseph (Open Humanities Press, 2021)
Joseph Nechvatal's Immersion Into Noise investigates multiple aspects of cultural noise by applying our audio understanding of noise to the visual, architectual and cognative domains. The author takes the reader through phenomenal aspects of the art of noise into algorithmic and network contexts, beginning in the Abside of the Grotte de Lascaux.